A tiphiid wasp Myzinum maculata Fabricius (Insecta: Hymenoptera: Tiphiidae: Myzininae) - Donald Spence; Amanda Hodges (EDIS, 2010)
EENY-470, a 5-page illustrated fact sheet by Donald Spence and Amanda Hodges, is part of the Featured Creatures collection. It describes this wasp species commonly found in Florida — distribution, description, life cycle, hosts, and economic importance. Includes references. Published by the UF Department of Entomology and Nematology, June 2010.